2002
DOI: 10.1152/ajpheart.00640.2001
|View full text |Cite
|
Sign up to set email alerts
|

Decrease in cardiac output and muscle sympathetic activity during vasovagal syncope

Abstract: The importance of cardiac output (CO) to blood pressure level during vasovagal syncope is unknown. We measured thermodilution CO, mean blood pressure (MBP), and leg muscle mean sympathetic nerve activity (MSNA) each minute during 60 degrees head-up tilt in 26 patients with recurrent syncope. Eight patients tolerated tilt (TT) for 45 min (mean age 60 +/- 5 yr) and 15 patients developed syncope during tilt (TS) (mean age 58 +/- 4 yr, mean tilt time 15.4 +/- 2 min). In TT patients, CO decreased during the first m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
61
1
3

Year Published

2003
2003
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(74 citation statements)
references
References 39 publications
9
61
1
3
Order By: Relevance
“…For both men and women, MAP remained relatively stable during progressive LBNP until hemodynamic collapse and prominent hypotension occurred suddenly. There was not a threshold BP that was reached earlier in women, but rather a neurally mediated event, presumably sympathetic withdrawal (20,25,49), that occurred when the heart was markedly unloaded.…”
Section: The Frank-starling Relation and Its Implication For Orthostamentioning
confidence: 99%
See 2 more Smart Citations
“…For both men and women, MAP remained relatively stable during progressive LBNP until hemodynamic collapse and prominent hypotension occurred suddenly. There was not a threshold BP that was reached earlier in women, but rather a neurally mediated event, presumably sympathetic withdrawal (20,25,49), that occurred when the heart was markedly unloaded.…”
Section: The Frank-starling Relation and Its Implication For Orthostamentioning
confidence: 99%
“…Thus, although not dispositive, the weight of evidence suggests that the absence of any differences between genders in norepinephrine or total peripheral resistance, which is the ultimate downstream determinant of the effect of increasing sympathetic nerve activity, argues against a physiologically meaningful impairment in vasomotor control in women. Numerous investigations have shown that the ultimate precipitant of hypotension and syncope is sympathetic withdrawal and vasodilation (10,24,25,45). Although the exact stimulus that causes this final common pathway is unknown, it has been argued that stimulation of ventricular mechanoreceptors in the setting of a small, hypercontractile heart may be one potential mechanism (26,33,37).…”
Section: Vascular Resistance Responses During Orthostatic Stress In Wmentioning
confidence: 99%
See 1 more Smart Citation
“…[16,17] The temporal sequence of changes in blood pressure and heart rate during tilt induced syncope parallel those seen with spontaneous syncope. [18] Single-stage isoproterenol tilt table test has been found to be more effective in inducing a positive vasovagal response in an adult population than the standard (drug free) passive tilt table test, and it significantly reduced the procedural time. [19] These observations are in agreement with our study.…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, more than 2 decades ago, VVS was reported in heart transplant recipients and more recently several investigators made the observation that decreases in cardiac output contributed to the hypotension independent of reflex-mediated changes [14,20,39]. Fu et al showed that up to one third of subjects with tilt induced pre-syncope had a severe drop in cardiac output with no change in total peripheral resistance.…”
Section: Pathophysiology Of Ttt Induced Syncopementioning
confidence: 99%